2012
DOI: 10.1007/s10853-012-6371-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of luminescent polycarbonate grafted with methyl methacrylate/europium complex using supercritical CO2 technology as a green chemistry method

Abstract: Modification of polymers using supercritical carbon dioxide (scCO 2 ) impregnation technology is an advantageous method for imparting desirable properties into a new polymer formulation without the architecture of the material being affected. Methyl methacrylate (MMA) and acrylic complex of europium [Eu(TTA) 3 AA] were impregnated on polycarbonate (PC) in the scCO 2 phase. There was an increase in the amount of grafted Eu(TTA) 3 AA complex up to 6 h of impregnation, reaching 0.24% of grafting. For longer times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…The monomer of DBHP was prepared by the modified literature procedure [17][18][19]. In the literature, mono-and dibenzoyl biphenols were obtained as the products, and they could be only separated by column chromatography, resulting in a low yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The monomer of DBHP was prepared by the modified literature procedure [17][18][19]. In the literature, mono-and dibenzoyl biphenols were obtained as the products, and they could be only separated by column chromatography, resulting in a low yield.…”
Section: Resultsmentioning
confidence: 99%
“…(3) Many researchers studied transparent ultrahydrophobic silica films modified alkoxysilane by the sol-gel process under UV irradiation [16]. Several authors reported to enhance the scratch resistance of polycarbonate with SiO 2 and TiO 2 using microwave-assisted sol-gel heating [17,18]. The morphology of the fabric with alkali treatment and polycarbonate coating was studied using the scanning electron microscopy and polarized optical microscopic techniques [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, for medical applications, the presence of toxic substances from the preparation process in the final materials is critical. Recently, there has attracted a lot of interesting in the synthesis and the processing of biomaterials and tissue engineering scaffold using supercritical carbon dioxide (scCO 2 ) as reaction media due to its low toxicity and inexpensive [3] . There are lots of works have reported synthesis of biodegradable polyester in scCO 2 .…”
Section: Introductionmentioning
confidence: 99%